Evaluating global health initiatives to improve health equity - El Arifeen, Shams; Grove, John; Hansen, Peter; Hargreaves, James; Johnson, Hope; Johri, Mira; Saville, Esther (Bulletin of the World Health Organization, 2024)
Global health initiatives are multistakeholder partnerships that mobilize and disburse resources to address global health challenges, often by supporting implementation of health programmes in low-and middle-income countries.1 These initiatives have made enormous contributions to saving lives and improving health globally, and are vital to the realization of sustainable development goal (SDG) 3 to ensure healthy lives and promote well-being for all at all ages.1,2 However, some members of the global health community have criticized the ways these initiatives work, notably in relation to power imbalances between donor and implementing partners in priority-setting and decision-making.1 These imbalances can translate into questions of whose knowledge, vision and voice drive organizational direction.We are writing as representatives of the evaluation units and evaluation advisory bodies of three prominent global health initiatives, to reflect on challenges and solutions to strengthening health equity via improved evaluation. As part of its mission to save lives and protect people's health by increasing equitable and sustainable use of vaccines, Gavi, the Vaccine Alliance, helps vaccinate almost half the world's children against deadly and debilitating infectious diseases.3 To ensure that all women, children and adolescents can survive and thrive, the Global Financing Facility for Women, Children and Adolescents, a multistakeholder global partnership housed at the World Bank, supports 36 low- and lower-middle-income countries with financing and technical assistance to develop and implement prioritized national health plans to scale up access to affordable, quality care.4 The Global Fund, a worldwide partnership to defeat human immunodeficiency virus, tuberculosis and malaria, and ensure a healthier, safer, more equitable future for all, works to fight the deadliest infectious diseases, challenge the injustices that fuel them and strengthen health systems in more than 100 countries. 5 In 2019, our organizations collectively raised and invested in excess of 6 billion United States dollars (US$), representing approximately 14% of all development assistance for health.6 In 2021, to strengthen the global response to the coronavirus disease 2019 (COVID- 19) pandemic, donors entrusted our organizations with more than US$ 14 billion, representing roughly 21% of all development assistance for health.6A core strategic focus for the global initiatives for health has been to improve access to essential vaccines, medicines and technologies for priority conditions. 1 The goal of Transforming our world: the 2030 agenda for sustainable development drives us also to advance through transformative policies with the potential to reshape underlying socioeconomic and political structures.7 Here we discuss how reshaping organizational evaluation processes can enable us to deliver better on our mandates and on the SDGs.